Oral colonization by yeasts in HIV-positive patients in Brazil - Junqueira, Juliana C.; Vilela, Simone F. G.; Rossoni, Rodnei D.; Barbosa, Júnia O.; Costa, Anna Carolina B. P.; Rasteiro, Vanessa M. C.; Suleiman, Jamal M. A. H.; Jorge, Antonio Olavo C. (Revista do Instituto de Medicina Tropical de São Paulo, 2012)
INTRODUCTION: In HIV-infected patients, colonization of the oral cavity by potential pathogenic yeast may lead to development of systemic fungemia. We evaluated the prevalence of yeast in the oral cavity of Brazilian HIV-positive patients and verified whether or not the species characterized were enzymatically active. Furthermore, the species identified were tested for their susceptibility to antifungal treatment. METHODS: Patient saliva and oropharyngeal candidiasis samples were collected from 60 seropositive HIV patients and identified by the API20C system. Enzymatic activity was evaluated by the production of proteinase and phospholipase. Susceptibility to antifungal treatments were determined using the broth microdilution method. RESULTS: the most commonly isolated species were C. albicans (51.56%) followed by non-albicans Candida species (43.73%), Trichosporon mucoides (3.12%) and Kodamaea ohmeri (1.56%). Oral colonization by association of different species was observed in 42% of the patients. Enzymatic activity was verified in most of species isolated, except for C. glabrata, C. lusitaniae and C. guilliermondii. Resistance to Fluconazole and Amphotericin B was observed in isolates of C. albicans, C. glabrata, C. parapsilosis, C. krusei, and K. ohmeri. CONCLUSION: HIV-positive patients are orally colonized by single or multiple species of yeast that are occasionally resistant to Fluconazole or Amphotericin B.